2009
DOI: 10.1080/10253890802042041
|View full text |Cite
|
Sign up to set email alerts
|

Chronic work stress and exhaustion is associated with higher allostastic load in female school teachers

Abstract: Epidemiological studies have shown that chronic work stress or unfavourable psychosocial work conditions are prospectively associated with different adverse health outcomes. The aim of the present cross-sectional study was to investigate the relationship between work-related chronic stress as well as exhaustion and a cumulative measure of physiological wear-and-tear called allostastic load (AL). AL could be a possible biological pathway for how chronic work stress and exhaustion lead to health impairments in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
126
3
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(154 citation statements)
references
References 66 publications
(89 reference statements)
15
126
3
7
Order By: Relevance
“…Finally, a summary index of stress-related biological markers of 'allostatic load' has been proposed by McEwen [31], indicating increased susceptibility to cardiovascular risk and disease. In a study on female teachers it was demonstrated that the group scoring high on ERI measures exhibited a significantly higher mean score than the less stressed group [39]. Taken together, naturalistic and experimental studies supplement epidemiological evidence by demonstrating psychobiological processes that possibly mediate the observed associations of psychosocial adversity at work with cardiovascular disease.…”
Section: Methodsmentioning
confidence: 71%
“…Finally, a summary index of stress-related biological markers of 'allostatic load' has been proposed by McEwen [31], indicating increased susceptibility to cardiovascular risk and disease. In a study on female teachers it was demonstrated that the group scoring high on ERI measures exhibited a significantly higher mean score than the less stressed group [39]. Taken together, naturalistic and experimental studies supplement epidemiological evidence by demonstrating psychobiological processes that possibly mediate the observed associations of psychosocial adversity at work with cardiovascular disease.…”
Section: Methodsmentioning
confidence: 71%
“…The teaching profession has been labeled as highly stressful [30,31] and such exposure may elevate the risk for mental and physical health problems [32,33]. Moreover relationships between mental and physical health components have already been investigated and demonstrated on several occasions [34].…”
Section: Discussionmentioning
confidence: 99%
“…The current review does not provide meta-analytical estimates since the available data did not meet the criteria for homogeneity in methods used to assess job strain and ERI, confounders, outcome measures, and biases potentially affecting internal validity. Our review however provides an in-depth analysis of several potential explanations for data inconsistencies (ie, gender, study design, types of BP measures, instruments for measuring psychosocial factors, categorization of exposure to psychosocial fac- (149,185,190) 0 / 0 0/0 1 (191) / 1 (191) 1 / 4 BP level 1 (189) / 2 (183,189) 0 / 0 0/0 1 (191) / 1 (191) 2 / 3 Men Hypertension 4 (184)(185)(186)190) / 4 (184)(185)(186)190) 0 / 0 0/0 0 / 1 (191) 4 / 5 BP level 0 / 0 1 (188) / 1 (188) 0/0 0 / 1 (191) 1 / 2 tors, control for potentially confounding factors, and participation rate). Such analysis allowed the identification of "optimal" methods to consistently observe the deleterious effect of psychosocial work factors on BP, namely the use of a prospective design and ambulatory BP measures.…”
Section: Methodological Characteristicsmentioning
confidence: 99%